Nano boron-loaded two-dimensional material compound as well as preparation method and application thereof

By combining nanoboro with two-dimensional materials, nanoboro-loaded two-dimensional material composites were prepared, which solved the problem of electrochemical inertia of pure boron and achieved the high energy density and power performance of lithium-ion batteries.

CN119581541AInactive Publication Date: 2025-03-07ZHONGBEI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411736264.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Pure boron has electrochemical inertia at room temperature, resulting in poor circulation performance and small battery capacity of lithium-ion batteries.

Method used

Nanoborbol is prepared by compositeing nanoboron with a two-dimensional material. The preparation method of the composite includes ultrasonic crushing of boron powder and etchant in an organic solvent, adding antioxidants, mixing and drying, and finally uniformly distribute with the two-dimensional material monolayer dispersion to form a composite.

Benefits of technology

This composite can effectively activate the electrochemical properties of boron, improve the energy density and power performance of lithium-ion batteries, and has a simple process, low synthesis temperature and high phase purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581541A_ABST
    Figure CN119581541A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery negative electrode materials, in particular to a nano-boron-loaded two-dimensional material compound and a preparation method and application thereof. The preparation method of the nano-boron-loaded two-dimensional material compound comprises the following steps: S1, jointly dissolving boron powder and an etching agent in an organic solvent, carrying out ultrasonication, then adding an antioxidant, stirring, centrifuging, and taking supernate to obtain a nano-boron solution; s2, adding a surfactant into the two-dimensional material single-layer dispersion liquid, uniformly mixing, adding into the nano-boron solution, stirring under the condition of protective gas, and finally drying to obtain the nano-boron loaded two-dimensional material compound. The nano boron loaded two-dimensional material compound provided by the invention has the advantages of simple process, low synthesis temperature, uniform chemical components of synthesized powder, good crystal morphology, high phase purity and the like. And when being used as a negative electrode material, the composite material has a better activation effect on electrochemical inertness of boron, so that the battery has relatively high energy density and power performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a nano-boron-loaded two-dimensional material composite and a preparation method and application thereof. Background Art

[0002] Boron has gained attention due to its extremely high theoretical lithium storage capacity. Boron is the lightest element that can form an alloy with lithium, except for the highly toxic beryllium. Theoretical calculations and simulations have proven that Li5B clusters can exist stably, so the theoretical capacity of B can reach 12395 mAhg -1 , is the negative electrode material of lithium battery with the largest theoretical capacity. However, pure boron is electrochemically inert at room temperature. Direct use as the negative electrode material of the battery often has defects such as poor cycle performance and small battery capacity. Therefore, it is urgent to study a boron composite negative electrode material that can improve the battery cycle performance and capacity. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a nano-boron-loaded two-dimensional material composite and its preparation method and application. The nano-boron-loaded two-dimensional material composite has the advantages of simple process, low synthesis temperature, uniform chemical composition of synthesized powder, good crystal morphology, high phase purity, etc. When used as a negative electrode material, it can have a better activation effect on the electrochemical inertness of boron, so that the battery has both high energy density and power performance.

[0004] To this end, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing a nano-boron-loaded two-dimensional material composite in an optional embodiment, comprising the following steps: S1: dissolving boron powder and an etchant in an organic solvent, performing ultrasonic crushing, then adding an antioxidant, stirring and centrifuging, and taking the supernatant to obtain a nano-boron solution; S2: After adding a surfactant to the two-dimensional material monolayer dispersion and mixing well, adding the surfactant to the nano-boron solution, stirring under protective gas conditions, and finally drying to obtain a nano-boron-loaded two-dimensional material composite.

[0005] In the present invention, the nano boron-loaded two-dimensional material composite has the advantages of simple process, low synthesis temperature, uniform chemical composition of the synthesized powder, good crystal morphology, high phase purity, etc. When used as a negative electrode material, it can have a better activation effect on the electrochemical inertness of boron.

[0006] The preparation method of the two-dimensional material monolayer dispersion liquid is: dissolving the two-dimensional material in deionized water and ultrasonically dispersing the two-dimensional material to obtain the two-dimensional material monolayer dispersion liquid.

[0007] Preferably, the mass ratio of the boron powder to the etchant is 1.5~2.5:2.5~3.5, preferably 2:3; and / or, the mass ratio of the boron powder to the antioxidant is 1.5~2.5:2.5~3.5, preferably 2:3; and / or, the mass ratio of the two-dimensional material to the surfactant is (4~6):(1~3); the mass ratio of the two-dimensional material monolayer dispersion to the nano-boron solution is 1:1~2. The etchant is selected from one or more of boric acid and hydrogen peroxide; and / or, the organic solvent is selected from one or more of isopropanol, N,N-dimethylformamide, nitrogen methyl pyrrolidone, and n-butanol, preferably isopropanol; and / or, The antioxidant is sodium borohydride. The surfactant is selected from one or more of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, sodium triacetoxyborohydride, and tetradecyltrimethylammonium bromide, preferably hexadecyltrimethylammonium bromide; and / or, the two-dimensional material is selected from one or more of Ti3C2, graphene, and borane, preferably Ti3C2. The concentration of the two-dimensional material monolayer dispersion is 3-7 mg / mL, preferably 5 mg / mL; and / or, the protective gas is selected from one of nitrogen and argon, preferably nitrogen.

[0008] In the present invention, the antioxidant is sodium borohydride, which is added after ultrasonic crushing and before stirring. The boric acid in the etchant has basically combined with the boron quantum dots to form a nano-boron solution. At this time, the sodium borohydride added will first be hydrolyzed into sodium metaborate and hydrogen. Its strong reducing property can be used as an antioxidant in the solution system. Due to the electron-deficient characteristics of boron salts, the boron in the by-product will also be added to the nano-boron and give the boron quantum dots higher electrochemical activity. The hydrogen generated after hydrolysis can also provide a condition for removing oxygen from the preparation system.

[0009] Preferably, in step S1, the stirring time is not less than 12 hours; the stirring can be carried out by magnetic stirring, or other stirring methods that can stir the boron powder, etchant and organic solvent uniformly, and / or, in step S2, the stirring time is not less than 8 hours. The drying can be carried out by freeze drying, or other methods that can dry the composite. If freeze drying is selected, the drying temperature is (-53) ~ (-48) ° C, the pressure is <10Pa, and the time is 36~48 hours.

[0010] In a second aspect, the present invention provides, in an optional embodiment, a nano-boron-loaded two-dimensional material composite, which is prepared using the above-mentioned preparation method.

[0011] In a third aspect, the present invention provides, in an optional embodiment, an application of the above-mentioned nano-boron-loaded two-dimensional material composite as a negative electrode material for a lithium-ion battery.

[0012] In a fourth aspect, the present invention provides, in an optional embodiment, a negative electrode material for a lithium-ion battery, comprising the above-mentioned nano-boron-loaded two-dimensional material composite, a conductive agent and a binder.

[0013] In the present invention, the conductive agent includes but is not limited to carbon black, conductive graphite, carbon nanotubes, graphene, and acetylene black, and the binder includes but is not limited to polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber latex, polyacrylic acid, polyacrylonitrile, and sodium alginate.

[0014] In a fifth aspect, the present invention provides a lithium-ion battery in an optional embodiment, comprising the above-mentioned lithium-ion battery negative electrode material, positive electrode material, separator and electrolyte.

[0015] In the present invention, the positive electrode material includes but is not limited to lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron phosphate, nickel cobalt manganese oxide, and nickel cobalt aluminum oxide. The diaphragm includes but is not limited to polyethylene diaphragm, polypropylene diaphragm, and polyimide film. The electrolyte includes but is not limited to lithium hexafluorophosphate electrolyte, lithium tetrafluoroborate electrolyte, and lithium bis(oxalatoborate) electrolyte.

[0016] In the present invention, the negative electrode capacity of lithium-ion batteries made of nano-boron-loaded two-dimensional material composites provided by the present invention exceeds that of individual boron quantum dots or Ti3C2. The present invention evenly distributes two nano-materials with excellent electrochemical properties to solve the inherent agglomeration and stacking of nano-materials. The electrochemical performance advantages of high theoretical capacity of boron and high conductivity and multiple active sites of MXenes are better utilized.

[0017] Compared with the prior art, the present invention has one of the following beneficial effects: 1. The nano boron-loaded two-dimensional material composite provided by the present invention has the advantages of simple process, low synthesis temperature, uniform chemical composition of the synthesized powder, good crystal morphology, high phase purity, etc. When used as a negative electrode material, it can have a better activation effect on the electrochemical inertness of boron.

[0018] 2. The negative electrode capacity of lithium-ion batteries made of nano-boron-loaded two-dimensional material composites provided by the present invention exceeds that of single boron quantum dots or Ti3C2. The present invention evenly distributes two nano-materials with excellent electrochemical properties, solving the inherent agglomeration and stacking phenomena of nano-materials. The electrochemical performance advantages of high theoretical capacity of boron and high conductivity and multiple active sites of MXenes are better utilized.

[0019] 3. The layered nano-boron-loaded two-dimensional material composite provided by the present invention has a high material utilization rate, and various precursors, surfactants, etc. are converted into final electrode materials, achieving the purpose of green environmental protection and sustainability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is a schematic diagram of the process of preparing the nano-boron-loaded two-dimensional material composite obtained in Example 1 of the present invention; Figure 2 This is an X-ray diffraction (XRD) test result diagram of the nano-boron-loaded two-dimensional material composite, boron element and monolayer Ti3C2 prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope (SEM) test result diagram of the nano-boron-loaded two-dimensional material composite and the single-layer Ti3C2 prepared in Example 1 of the present invention; Figure 4 This is a transmission electron microscope (TEM) test result diagram of the nano-boron-loaded two-dimensional material composite prepared in Example 1 of the present invention; Figure 5 This is a graph showing the electrochemical performance test results of the nano-boron-loaded two-dimensional material composite prepared in Example 1 of the present invention; Figure 6 This is the electrochemical performance test result diagram of single-layer Ti3C2; Figure 7 This is the test result of electrochemical performance of boron powder; Figure 8 This is the electrochemical performance test result diagram of nano-boron solution; Fig. 9 This is a graph showing the electrochemical performance test results of the nano-boron-loaded two-dimensional material composite, single-layer Ti3C2 and boron powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] Pure boron is electrochemically inert at room temperature, but if it is reduced to quantum size (quantum dots) and combined with two-dimensional materials, the electrochemical activity of boron can be improved. Two-dimensional transition metal carbon / nitride (MXenes), as a new type of two-dimensional material with graphene-like structure, has been proven to be a competitive high-performance electrode material. x (MXene) phase due to its low cost, high conductivity (6500 S cm-1 ) and low lithium ion transport barrier (0.07 eV), etc., it stands out in the MXenes family and becomes a new research hotspot. In addition, boron quantum dots can introduce defects to attract positive ions, improve the diffusion and storage of lithium ions, reduce the gap distance, and increase the conductivity. Therefore, the present invention combines boron quantum dots and MXenes materials, and uses this combination as a starting point to solve the inherent problems such as quantum dot agglomeration and MXenes self-stacking.

[0024] The technical solution of the present invention will be further described below in conjunction with specific implementation methods.

[0025] Example 1: Combination Figure 1 This embodiment provides a method for preparing a nano-boron-loaded two-dimensional material composite, comprising the following steps: S1: Boric acid, boron powder and hydrogen peroxide solution are weighed in a ratio of 2:3 between boron powder and etchant (wherein the ratio of the mixed solution of boric acid and hydrogen peroxide is 200 mg of boric acid and 3 mL of 3% hydrogen peroxide solution), and they are dissolved in 50 mL of isopropanol solution. After mixing evenly, they are crushed in an ultrasonic crusher. Then, sodium borohydride is weighed in a ratio of 2:3 between boron powder and antioxidant. Finally, the mixture is stirred by magnetic stirring for 12 h, and the supernatant is centrifuged to obtain a nano-boron solution. S2: After adding 40 mg of hexadecyltrimethylammonium bromide to 20 mL of 5 mg / mL Ti3C2 monolayer dispersion stored in an oxygen-free and weak-light environment and stirring thoroughly, 20 mL of nanoboron solution was added, stirred for 12 h under a nitrogen atmosphere, and finally placed in a freeze dryer for drying (temperature of -53 °C, pressure below 5 Pa, time for 24 h) to obtain a nanoboron-loaded two-dimensional material composite, recorded as nanoboron solution / d-Ti3C2.

[0026] Example 2: This example provides a method for preparing a nano-boron-loaded two-dimensional material composite, comprising the following steps: S1: Boric acid, boron powder and hydrogen peroxide solution are weighed in a ratio of 2:3 between boron powder and etchant (wherein the ratio of the mixed solution of boric acid and hydrogen peroxide is 200 mg of boric acid and 3 mL of 3% hydrogen peroxide solution), and they are dissolved in 50 mL of isopropanol solution. After mixing evenly, they are crushed in an ultrasonic crusher. Then, sodium borohydride is weighed in a ratio of 2:3 between boron powder and antioxidant. Finally, the mixture is stirred by magnetic stirring for 12 h, and the supernatant is centrifuged to obtain a nano-boron solution. S2: After adding 40 mg of hexadecyltrimethylammonium bromide to 20 mL of Ti3C2 monolayer dispersion with a mass fraction of 7 mg / mL stored in an oxygen-free and weak-light environment and stirring thoroughly, 20 mL of nanoboron solution was added, stirred for 12 hours under a nitrogen atmosphere, and finally placed in a freeze dryer for drying (temperature of -53 °C, pressure below 5 Pa, time for 24 hours) to obtain a nanoboron-loaded two-dimensional material composite, recorded as nanoboron solution / d-Ti3C2.

[0027] Example 3: This example provides a method for preparing a nano-boron-loaded two-dimensional material composite, comprising the following steps: S1: Boric acid, boron powder and hydrogen peroxide solution are weighed in a ratio of 2:3 between boron powder and etchant (wherein the ratio of the mixed solution of boric acid and hydrogen peroxide is 200 mg of boric acid and 3 mL of 3% hydrogen peroxide solution), and they are dissolved in 50 mL of isopropanol solution. After mixing evenly, they are crushed in an ultrasonic crusher. Then, sodium borohydride is weighed in a ratio of 2:3 between boron powder and antioxidant. Finally, the mixture is stirred by magnetic stirring for 12 h, and the supernatant is centrifuged to obtain a nano-boron solution. S2: After adding 40 mg of hexadecyltrimethylammonium bromide to 20 mL of 3 mg / mL Ti3C2 monolayer dispersion stored in an oxygen-free and weak-light environment and stirring thoroughly, 20 mL of nanoboron solution was added, stirred for 12 h under a nitrogen atmosphere, and finally placed in a freeze dryer for drying (temperature of -53 °C, pressure below 5 Pa, time for 24 h) to obtain a nanoboron-loaded two-dimensional material composite, recorded as nanoboron solution / d-Ti3C2.

[0028] Experimental Example: X-ray diffraction (XRD) tests were performed on the boron nano-boron solution, the monolayer Ti3C2 and the nano-boron-loaded two-dimensional material composite prepared in Example 1. The results are shown in Figure 2 .

[0029] pass Figure 2 It can be seen that in the XRD curve, the characteristic peak of the single-layer Ti3C2 is at a diffraction angle of 2θ=6.340°, while the characteristic peak of the composite Ti3C2 shifts to the left at a diffraction angle of 2θ=1.439°. According to the Bragg law, when the characteristic peak shifts to the left, the interlayer spacing of Ti3C2 increases. This may be due to the distribution of the nano-boron solution on the surface of MXenes, which weakens the van der Waals force between Ti3C2 layers and increases the interlayer spacing. It also proves from the side that the addition of the nano-boron solution can well avoid the self-stacking of the Ti3C2 layers.

[0030] The single-layer Ti3C2 and the nano-boron-loaded two-dimensional material composite prepared in Example 1 were examined by scanning electron microscopy (SEM). Figure 3 .

[0031] pass Figure 3 It can be seen that: Figure 3 .1, the single layer Ti3C2 before composite is clearly distributed between layers, and the surface is mostly smooth with few defects, while Figure 3 .2, due to the addition of nano-boron solution, the surface of Ti3C2 becomes rough, which may increase the specific surface area of ​​the composite, thereby reducing the initial coulombic efficiency. Therefore, the low initial efficiency of the electrode of the present invention may be attributed to the increase in specific surface area after the composite. Figure 3 .3, it can be seen that the distribution between the single-layer Ti3C2 layers is obvious, which is attributed to the introduction of nano-boron solution, which weakens the van der Waals force between the single-layer Ti3C2 and does not form self-stacking.

[0032] The nano-boron-loaded two-dimensional material composite prepared in Example 1 was tested by transmission electron microscopy (TEM). Figure 4 .

[0033] pass Figure 4 Typical single-piece MXenes stripes can be seen, and there are boron quantum dots of about 4-6 nm evenly distributed on the MXenes layer structure. This shows that nano-boron solution / d-Ti3C2 has been successfully composited.

[0034] Select boron nano-boron solution, boron powder, monolayer Ti3C2, and the nano-boron-loaded two-dimensional material composite prepared in Example 1, a conductive agent (acetylene black), and a binder (PVDF) in a mass ratio of 8:1:1 and pour them into a clean agate mortar for grinding until the viscous liquid is found to have a metallic reflective color and is relatively uniform; then drip or apply the ground slurry to the surface of the copper foil, and place the coated copper foil in a clean vacuum drying oven for drying. Cut off the unused part of the dried copper foil, weigh the mass, and assemble the battery in the glove box. Then test the battery capacity and performance. See the test results for details. Figure 5-Figure 9 The test results of the nano boron-loaded two-dimensional material composite prepared in Example 1 are as follows: Figure 5 As shown, the test results of single-layer Ti3C2 are as follows Figure 6 The test results of boron powder are shown in Figure 7 As shown, the test results of nano boron solution are as follows Figure 8 shown.

[0035] pass Figure 5 It can be seen that the battery made of the prepared material has certain battery performance. From the charge and discharge curve, it can be seen that the discharge / charge capacity of the first cycle is 730.1 mAhg -1 and 344.9 mAhg -1The initial coulombic efficiency is 33.68%. In the subsequent cycles, the capacity gradually stabilizes and the coulombic efficiency gradually approaches 100%. In the 13th cycle, the discharge capacity stabilizes at 299.3 mAhg -1 , the Coulombic efficiency is 97.55%, indicating that the insertion and deinsertion of lithium ions in this material is highly reversible. Figure 5 In the long cycle diagram, the capacity is 290 mAhg from 13 to 71 cycles. -1 The baseline fluctuates up and down. This is attributed to the loss of capacity due to changes in electrolyte and electrode materials during the charge and discharge process. However, the activity of boron quantum dots is constantly stimulated, and a large number of boron quantum dots begin to participate in the storage of lithium ions, causing capacity fluctuations. After about 71 cycles, the battery capacity began to increase from 292.5 mAhg -1 Steadily improving, the most recent data recorded in the 115th cycle has reached 317.3 mAhg -1 It also shows that the high conductivity MXenes in the prepared composite stimulated the super-strong lithium storage capacity of boron, making it show good lithium storage performance, indicating that it has a certain cycle stability.

[0036] pass Figure 8 It can be seen that the coulombic efficiency and cycle number of the boron nano-boron solution are worse than those of the nano-boron-loaded two-dimensional material composite prepared in Example 1. This is because the nano-boron solution will form agglomerates after leaving the solution, so that fewer active sites can be provided, and due to the inherent electron deficiency and semiconductor properties of boron, the excellent electrochemical properties of boron cannot be exerted, resulting in poor performance of the final electrode, which cannot form a continuous conductive network like the composite.

[0037] Although the principles of the present invention are described in detail above in conjunction with the preferred embodiments of the present invention, those skilled in the art should understand that the above embodiments are merely explanations of the exemplary implementations of the present invention, and are not intended to limit the scope of the present invention. The details in the embodiments do not constitute limitations on the scope of the present invention, and any obvious changes such as equivalent transformations, simple replacements, etc. based on the technical solution of the present invention, without departing from the spirit and scope of the present invention, fall within the protection scope of the present invention.

Claims

1. A method for preparing a nano-boron-loaded two-dimensional material composite, characterized in that: The following steps are involved: S1: dissolving boron powder and an etchant in an organic solvent, performing ultrasonic crushing, then adding an antioxidant, stirring and centrifuging, and taking the supernatant to obtain a nano-boron solution; S2: After adding a surfactant to the two-dimensional material monolayer dispersion and mixing well, adding the surfactant to the nano-boron solution, stirring under protective gas conditions, and finally drying to obtain a nano-boron-loaded two-dimensional material composite.

2. The method for preparing the nano-boron-loaded two-dimensional material composite according to claim 1, characterized in that: The mass ratio of the boron powder to the etchant is 1.5-2.5:2.5-3.5; and / or, The mass ratio of the boron powder to the antioxidant is 1.5-2.5:2.5-3.5; and / or, The mass ratio of the two-dimensional material and the surfactant is (4-6): (1-3); and / or, The mass ratio of the two-dimensional material monolayer dispersion liquid to the nano-boron solution is 1:1-2.

3. The method for preparing the nano-boron-loaded two-dimensional material composite according to claim 1, characterized in that: The etchant is selected from one or more of boric acid and hydrogen peroxide; and / or, The organic solvent is selected from one or more of isopropanol, N,N-dimethylformamide, nitrogen methyl pyrrolidone, and n-butanol; and / or, The antioxidant is sodium borohydride.

4. The method for preparing the nano-boron-loaded two-dimensional material composite according to claim 1, characterized in that: The surfactant is selected from one or more of hexadecyltrimethylammonium bromide, sodium triacetoxyborohydride, and tetradecyltrimethylammonium bromide; and / or, The two-dimensional material is selected from one or more of Ti3C2, graphene, and borophene.

5. The method for preparing the nano-boron-loaded two-dimensional material composite according to claim 1, characterized in that: The concentration of the two-dimensional material monolayer dispersion is 3-7 mg / mL; and / or, The protective gas is selected from nitrogen and argon.

6. The method for preparing the nano-boron-loaded two-dimensional material composite according to claim 1, characterized in that: In step S1, the stirring time is not less than 12 hours; and / or, In step S2, the stirring time is not less than 8 hours.

7. A nano-boron-loaded two-dimensional material composite, characterized in that: The preparation method is described in any one of claims 1 to 6.

8. Use of the nano-boron-loaded two-dimensional material composite according to claim 7 as a negative electrode material for lithium-ion batteries.

9. A negative electrode material for a lithium ion battery, characterized in that: It comprises the nano boron-loaded two-dimensional material composite as described in claim 7, a conductive agent and a binder.

10. A lithium ion battery, characterized in that: The invention comprises the negative electrode material, positive electrode material, separator and electrolyte of the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Boron quantum dot, and stabilizing treatment method and application thereof

    CN111217375A

  • Graphene / MXene superlattice composite electrode and preparation method and application thereof

    CN118888769A